Exercise intensity during competition time trials in professional road cycling - Padilla, S.; Mujika, I.; Orbananos, J.; Angulo, F. (Medicine & Science in Sports & Exercise, 2000)
To estimate, upon competition heart rate (HR), exercise intensity during time trials (TT) in professional road cycling. Methods: Eighteen world-class cyclists completed an incremental laboratory cycling test to assess maximal power output (Wmax), maximal HR (HRmax), onset of blood lactate accumulation (OBLA), lactate threshold (LT), and a HR-power output relationship. An OBLAZONE (HROBLA ± 3 beats·min-1) and a LTZONE (HRLT ± 3 beats·min-1) were described. HR was monitored during 12 prologue (<10 km, PTT), 18 short (<40 km, STT), 19 long (>40 km, LTT), eight uphill (UTT), and seven team (TTT) time trials. A HR-power output relationship was computed to estimate each cyclist's power output during TT racing from competition HR. Competition training impulse (TRIMP) values were estimated from HR and race duration. Results: %HRmax were 89 ± 3%, 85 ± 5%, 80 ± 5%, 78 ± 3%, and 82 ± 2% in PTT, STT, LTT, UTT, and TTT, respectively. The amount of TRIMP were, respectively, 21 ± 3, 77 ± 23, 122± 27, 129 ± 14, and 146 ± 6. Competition HR values relative to HROBLA and HRLT were, respectively, 100 ± 3%, 114 ± 8% in PTT, 95 ± 7%, 108 ± 9% in STT, 89 ± 5%, 103 ± 8% in LTT, 87 ± 2%, 101 ± 5% in UTT, and 91 ± 4%, 105 ± 11% in TTT. Conclusions: %HRmax, TRIMP and time distribution around HROBLA and HRLT reflected the physiological demands of different TT categories. HROBLA and HRLT were accurate intensity markers in events lasting, respectively, <30 (PTT and STT) and >30 min (LTT, UTT, TTT).